2010
DOI: 10.1143/jpsj.79.063706
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of X-ray Irradiated Organic Mott Insulator κ-(BEDT-TTF)2Cu[N(CN)2]Cl

Abstract: We have performed static magnetic susceptibility and ESR measurements on the X-ray-irradiated organic Mott insulator -(BEDT-TTF) 2 Cu[N(CN) 2 ]Cl. The Néel temperature and the spin-flop transition field decrease with increasing irradiation dose. In the ESR signal at 4 K, a paramagnetic component ($15%) from itinerant carriers appears after irradiation in addition to the parent antiferromagnetic ($85%) and minor paramagnetic localized spin components. We propose that domains of the itinerant carriers with a siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Usually charged defects effectively increase the spin relaxation rate in conductors. The insensitivity of T 2 to irradiation and the relatively small decrease in T x are in agreement with earlier findings [9] that the concentration of induced defects is small even under the largest dose. 2 at 50 K Figure 6 displays the irradiation dependence of the ESR spectra at 222.4 GHz and the spin relaxation times.…”
Section: Interlayer Hopping Rate and Resistivity Above The Metal Insusupporting
confidence: 92%
See 3 more Smart Citations
“…Usually charged defects effectively increase the spin relaxation rate in conductors. The insensitivity of T 2 to irradiation and the relatively small decrease in T x are in agreement with earlier findings [9] that the concentration of induced defects is small even under the largest dose. 2 at 50 K Figure 6 displays the irradiation dependence of the ESR spectra at 222.4 GHz and the spin relaxation times.…”
Section: Interlayer Hopping Rate and Resistivity Above The Metal Insusupporting
confidence: 92%
“…This study follows previous optical, resistivity, static magnetization and low frequency (9 GHz) ESR measurements on irradiated κ-ET 2 -Cl [6,9] and κ-ET 2 -Br [10] crystals at Tohoku University (Sendai, Japan). The method of irradiation has been described earlier [6].…”
Section: Methodssupporting
confidence: 58%
See 2 more Smart Citations
“…Actually, the molecular disorder introduced by X-ray irradiation to the organic superconductor κ-(BEDT-TTF) 2 Cu(NCS) 2 increases the residual resistivity, and suppresses the superconductivity [18,27]. We investigated the X-ray irradiation effect widely in κ-(BEDT-TTF) 2 X showing superconductivity or Mott insulating state from the viewpoint of the relation between the correlated electronic states and randomness [20,[27][28][29][30][31][32][33][34]. Recently, we found that the weak molecular disorder introduced by X-ray irradiation of the organic superconductor κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Br induced the Anderson-type localization insulating state from the strongly correlated metallic/superconducting state [31].…”
Section: Introductionmentioning
confidence: 99%